Terapi Okupasi Dalam Meningkatkan Keterampilan Motorik Halus Pada Anak Down Syndrome di Klinik Liliput - Muhammad Arief Effendi; Muhammad Sahrul (Jurnal Ventilator, 2024)
Down Syndrome is a fairly common genetic disorder, this is one of the diseases caused by the emergence of an extra chromosome from 21 pairs of chromosomes or known as trisomy 21. This study aims to determine the provision of Occupational Therapy in Down Syndrome Children at the Liliput Clinic. Occupational Therapy in Improving Fine Motor Skills in Down Syndrome Children and supporting and inhibiting factors. This study uses a Qualitative Method, the informant sampling technique uses the Purposive Sampling Technique. And data collection is obtained from the results of Interviews, Observations, and Documentation. Data analysis is carried out through the stages of Data Reduction, Data Presentation, and Conclusion Drawing. The location of this study is at the Liliput Clinic, Jl. Cipete IV No. 06, Rt. 02 Rw 03, South Cipete, Cilandak District. The results of the study showed that the provision of Occupational Therapy for Down Syndrome Children, namely, Down syndrome children still tend to be limp, such as when doing activities they get tired more easily, then Down syndrome children have not been able to regulate their emotions stably. In improving fine motor skills in Down syndrome children, therapists train and instruct children how to hold objects properly such as pencils, pens and small scissors. Then the child is instructed how to write correctly. Supporting factors in Occupational Therapy for Down Syndrome Children are an experienced therapy background, supporting infrastructure, and support from parents of Down syndrome children. And the inhibiting factors are Down syndrome children who have high emotional levels and physical problems in Down syndrome children.